'Team Learning' as an Innovative Pedagogical Tool:A Study among 'EE Generation' in Bangalore - John Manohar, S. (Journal of Engineering Education Transformations, 2025)
The concept of team learning has gained greater importance in modern Engineering Education and there are many formal recommendations to adopt team culture so as to groom them to face the real life situations after they graduate from Engineering Educational institutions. A descriptive study regarding the usefulness of team learning among 137 Engineering Education (EE) students was undertaken. The focus of the study was on contextual variables. Chi-square tests were employed and it was found that there exists association between and among all the variables considered for this study. It is strongly recommended that the Engineering students be provided with these opportunities so as to enable them to have hands on experience on managing a team in real life situations.